Professional Silverlight 4 - Beres, Jason (Wrox professional guides., 2010)
Everything .NET developers need to take advantage of Silverlight 4. Silverlight€4 is a major new release of Microsoft's flagship product for building rich, interactive applications that combine animation, graphics, audio, and video. This book, by seasoned Wrox authors and Silverlight experts, gives professional Web developers all the tools necessary to build RIAs using the new Silverlight capabilities. You will gain a complete, thorough understanding of both core and advanced platform concepts, with examples in both C♯ and VB.NET. Professional Silverlight 4 prepares Web developers to take.